2014
DOI: 10.1109/tsp.2014.2332447
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Random-Walk-Model-Based Kalman Filter for Slow to Moderate Fading Channel Estimation in OFDM Systems

Abstract: Abstract-This study deals with multi-path channel estimation for orthogonal frequency division multiplexing systems under slow to moderate fading conditions. Advanced algorithms exploit the channel time-domain correlation by using Kalman Filters (KFs) based on an approximation of the time-varying channel. Recently, it was shown that under slow to moderate fading, near optimal channel multi-path complex amplitude estimation can be obtained by using the integrated Random Walk (RW) model as the channel approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Each single-path KF is optimized by the channel state noise variance. It has been shown that the per-path processing KF can have almost the same performance as the joint multipath KF for the AR1 model [29], and this approximation has been analytically proved for RW models [28]. The per-path and joint multipath KF are identical when the discrete-time equivalent channel is uncorrelated, i.e., F H p F p = N p I L , or, equivalently, the multipath delays are multiples of the sample time, i.e., τ (l) are integers ( [28], appendix A).…”
Section: F Connection Between Rw-ls-catl and Rw-kf (Optimized In Jakmentioning
confidence: 90%
See 3 more Smart Citations
“…Each single-path KF is optimized by the channel state noise variance. It has been shown that the per-path processing KF can have almost the same performance as the joint multipath KF for the AR1 model [29], and this approximation has been analytically proved for RW models [28]. The per-path and joint multipath KF are identical when the discrete-time equivalent channel is uncorrelated, i.e., F H p F p = N p I L , or, equivalently, the multipath delays are multiples of the sample time, i.e., τ (l) are integers ( [28], appendix A).…”
Section: F Connection Between Rw-ls-catl and Rw-kf (Optimized In Jakmentioning
confidence: 90%
“…In general, λ > 1, while in the special case that F H p F p is a diagonal matrix equal to N p I L , one has λ = 1. This occurs only when the path delays of channel τ (l) T s are multiples of the sampling time T s , i.e., if the τ (l) are integers (see [28], appendix A for more details).…”
Section: B Error Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…This prompts the need for a comprehensive study of 2 Model (1) assumes that symbols are normalized and known (or decided), in addition to the flat fading assumption. Although this model is admittedly simplistic, it can be applied to different (more involved) contexts, such as pilot-aided multi-carrier systems in frequency-selective wireless channels [42]. channel estimation for f d T ≤ 10 −2 1 .…”
Section: True Channel Modelmentioning
confidence: 99%